2016
DOI: 10.1139/apnm-2015-0314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an acute bout of moderate-intensity exercise on postprandial lipemia and airway inflammation

Abstract: Obesity and asthma often coexist in the same people. Both are characterized by the presence of low-grade systemic inflammation. A high-fat diet may contribute to concurrent development of both conditions by promoting a pro-inflammatory postprandial environment leading to a transient accumulation of blood lipids (postprandial lipemia; PPL) and acute airway inflammation. Previous results from our lab have shown an ~20% increase in airway inflammation two hours after consuming a high-fat meal (HFM) that was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 106 publications
1
15
0
Order By: Relevance
“…TNF-α may increase postprandially in overweight participants [37], and in participants with metabolic syndrome [45]. However, other studies have reported no change [38, 46] or even a small decrease [35] in TNF-α postprandially. These conflicting results are most likely due to differences in participant characteristics between studies.…”
Section: Postprandial Inflammatory Responsementioning
confidence: 99%
See 2 more Smart Citations
“…TNF-α may increase postprandially in overweight participants [37], and in participants with metabolic syndrome [45]. However, other studies have reported no change [38, 46] or even a small decrease [35] in TNF-α postprandially. These conflicting results are most likely due to differences in participant characteristics between studies.…”
Section: Postprandial Inflammatory Responsementioning
confidence: 99%
“…Diet is obviously a very important factor to control leading up to a PPL session. The extent to which diet is controlled varies across studies, ranging from tightly controlled studies that provide meals for multiple days [76], to studies that only require participants to log food their food intake and/or keep meals consistent between trials [46]. However, even more important than controlling diet is the requirement of ensuring that individuals fast (for at least 8 h, but typically 10–12 h) prior to their test meal.…”
Section: Assessment Of Ppl and Postprandial Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after a single high-fat meal (HFM), airway inflammation (measured via exhaled nitric oxide (eNO) (Rosenkranz et al 2010; Johnson et al 2015)) and sputum neutrophils increase in non-asthmatic individuals (Kurti et al 2015). Researchers have also reported an increase in airway inflammation in asthmatic individuals (Wood et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that active, non-asthmatic individuals experience airway inflammation post-HFM, and an acute bout of exercise does not modify this response (Kurti et al 2015; Johnson et al 2015). However given that ROS can increase after a single HFM (Mohanty et al 2002; Tushuizen et al 2006) and may result in airway inflammation, individuals who are insufficiently active, with reduced antioxidant defenses, may have a greater magnitude of the cellular oxidative stress and inflammatory response to a HFM as compared to physically active individuals.…”
Section: Introductionmentioning
confidence: 99%